Exendin-4, a Glucagon-Like Peptide-1 Receptor Agonist, Reduces Alzheimer Disease-Associated Tau Hyperphosphorylation in the Hippocampus of Rats With Type 2 Diabetes. Issue 2 (1st February 2015) - Xu, Weijie; Yang, Yan; Yuan, Gang; Zhu, Wenjun; Ma, Delin; Hu, Shuhong
Abstract : Background: Impaired insulin signaling pathway in the brain in type 2 diabetes (T2D) is a risk factor for Alzheimer disease (AD). Glucagon-like peptide-1 (GLP-1) and its receptor agonist are widely used for treatment of T2D. Here we studied whether the effects of exendin-4 (EX-4), a long-lasting GLP-1 receptor agonist, could reduce the risk of AD in T2D. Materials and Methods: Type 2 diabetes rats were injected with EX-4 for 28 consecutive days. Blood glucose and insulin levels, as well as GLP-1 and insulin in cerebrospinal fluid, were determined during the experiment. The phosphorylation level of tau at individual phosphorylation sites, the activities of phosphatidylinositol 3 kinase/protein kinase B (PI3K/AKT), and glycogen synthase kinase-3β (GSK-3β) were analyzed with Western blots. Results: The levels of phosphorylated tau protein at site Ser199/202 and Thr217 level in the hippocampus of T2D rats were found to be raised notably and evidently decreased after EX-4 intervention. In addition, brain insulin signaling pathway was ameliorated after EX-4 treatment, and this result was reflected by a decreased activity of PI3K/AKT and an increased activity of GSK-3β in the hippocampus of T2D rats as well as a rise in PI3K/AKT activity and a decline in GSK-3β activity after 4 weeks intervention of EX-4. Conclusions: These results demonstrate that multiple days with EX-4 appears to prevent the hyperphosphorylation of AD-associated tau protein due to increased insulin signaling pathway in the brain. These findings support the potential use of GLP-1 for the prevention and treatment of AD in individuals with T2D.